Development of an Intuitive Glove-based Human Interface for Robotic Applications - Liddell, Harrison; Secco, Emanuele Lindo (Bio-Robotics, 2025)
This paper focuses on developing an innovative glove that enables users to control robots through natural hand gestures. The primary goal is to simplify human-robot interaction, allowing individuals to communicate with robots without extensive training or technical knowledge. The glove has three types of sensors: an ultrasonic sensor for measuring distances, flex sensors for tracking finger movements, and a GY-521 accelerometer for monitoring the hand's position and motion. By integrating these technologies, the glove translates simple hand gestures into precise commands for robotic systems, making it a powerful tool for various applications. To ensure the glove's effectiveness, the project began with a thorough review of existing research in human-robot interaction. This literature review helped identify the best features and methods to incorporate into the glove's design. The development process involved designing the glove, creating a prototype, and rigorously testing it to confirm that all sensors functioned correctly and that the glove was comfortable to wear. During the testing phase, each sensor was evaluated individually and combined with the others. The aim was to verify that they accurately captured data in real time and worked together seamlessly. The expected outcomes include the glove's ability to effectively recognize hand movements, detect objects, and allow users to control robots with ease. This project attempts to bridge the gap between human actions and robotic responses, making technology more accessible and user-friendly. In summary, the glove-based control system has the potential to transform how individuals interact with robots. By utilizing simple hand gestures, users can perform complex tasks more effortlessly, which could be particularly beneficial in fields such as healthcare, manufacturing, and assistive technology. The research aims to pave the way for more effective and engaging robotic systems that cater to a wide range of needs, enhancing how people live and work alongside technology.